Central nervous system immune-related disorders after SARS-CoV-2 vaccination: a multicenter study - Vogrig, Alberto; Tartaglia, Sara; Dentoni, Marta; Fabris, Martina; Bax, Francesco; Belluzzo, Marco; Verriello, Lorenzo; Bagatto, Daniele; Gastaldi, Matteo; Tocco, Pierluigi; Zoccarato, Marco; Zuliani, Luigi; et al. (Frontiers in Immunology, 2024)
Background: COVID-19 vaccines have been approved due to their excellent safety and efficacy data and their use has also permitted to reduce neurological complications of SARS-CoV-2. However, clinical trials were underpowered to detect rare adverse events. Herein, the aim was to characterize the clinical spectrum and immunological features of central nervous system (CNS) immune-related events following SARS-CoV-2 vaccination. Methods: Multicenter, retrospective, cohort study (December 1, 2020-April 30, 2022). Inclusion criteria were (1) de novo CNS disorders developing after SARS-CoV-2 vaccination (probable causal relationship as per 2021 Butler criteria); (2) evidence for an immune-mediated etiology, as per (i) 2016 Graus criteria for autoimmune encephalitis (AE); (ii) 2015 Wingerchuk criteria for neuromyelitis optica spectrum disorders; (iii) criteria for myelitis. Results: Nineteen patients were included from 7 tertiary referral hospitals across Italy and France (one of them being a national referral center for AE), over almost 1 year and half of vaccination campaign. Vaccines administered were mRNA-based (63%) and adenovirus-vectored (37%). The median time between vaccination and symptoms onset was 14 days (range: 2-41 days). CSF was inflammatory in 74%; autoantibodies were detected in 5%. CSF cytokine analysis (n=3) revealed increased CXCL-10 (IP-10), suggesting robust T-cell activation. The patients had AE (58%), myelitis (21%), acute disseminated encephalomyelitis (ADEM) (16%), and brainstem encephalitis (5%). All patients but 2 received immunomodulatory treatment. At last follow-up (median 130 days; range: 32-540), only one patient (5%) had a mRS>2. Conclusions: CNS adverse events of COVID-19 vaccination appear to be very rare even at reference centers and consist mostly of antibody-negative AE, myelitis, and ADEM developing approximately 2 weeks after vaccination. Most patients improve following immunomodulatory treatment.